KAMPANYE KOMUNIKASI PEMASARAN DALAM MENINGKATKAN PERFORMA MEDIA DIGITAL JATENG POS SEBAGAI ACCOUNT EXECUTIVE DAN EVENT MANAGER - Auryn Puan Karina; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
The rapid development of information and communication technology has encouraged Jateng Pos to adapt to a competitive digital environment. However, its digital media performance remained suboptimal, indicated by low website traffic, limited reach, and low engagement, particularly among Generation Z. Therefore, this field project aimed to improve Jateng Pos's digital performance through an Integrated Marketing Communication (IMC) approach and curated flows concept. The program was implemented through the “Jangan Cuma Klik Judulnya” campaign, “Creative News Challenge” competition, Jateng Pos Goes to School, media partnerships, and Instagram optimization. During the process, the author served as an Account Executive and Event Manager, responsible for client relationships, program coordination, and event execution. The campaign demonstrated significant improvements: Instagram reach increased from 893 to 113,718 accounts, followers grew from 3,763 to 4,670, engagement rate rose from 0.03% to 10.62%, and referred social traffic to the website rose from 373 to 1,182 visits. All Key Performance Indicators (KPIs) were successfully achieved, proving the campaign's effectiveness in strengthening connections with Generation Z audiences.